2016
DOI: 10.22302/iccri.jur.pelitaperkebunan.v32i3.217
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Wood Origin and Indole Butyric Acid Influence Success of Liberica Coffee Cuttings (Coffea Liberica W. Bull Ex. Hier)

Abstract: Liberica coffee can be grown in peatland and has a specific flavor. To anticipate high demand of Liberica coffee product, it is very important to support the availability of high quality seedlings that need effective multiplication method of superior genotypes. This study aimed to investigate the effect of indole-butyric acid (IBA) concentration and cuttings wood origin and their interaction in the success of Liberica coffee cuttings. This research was held at Kaliwining Experimental Station, Indonesian Coffee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This is in line with research in Robusta coffee, auxin in particularly NAA above 100 ppm reduces the number of leaves [17]. Based on Liberica coffee research by Erdiansyah [18], increasing the concentration of IBA decreases callus diameter. These data indicated that the influence of exogenous hormones at 12 WAP was decreased.…”
Section: Effect Of Coffee Species On Callus Diameter and Leaves Numbersupporting
confidence: 87%
“…This is in line with research in Robusta coffee, auxin in particularly NAA above 100 ppm reduces the number of leaves [17]. Based on Liberica coffee research by Erdiansyah [18], increasing the concentration of IBA decreases callus diameter. These data indicated that the influence of exogenous hormones at 12 WAP was decreased.…”
Section: Effect Of Coffee Species On Callus Diameter and Leaves Numbersupporting
confidence: 87%